POLA KOMUNIKASI INTERPERSONAL BAGI KELUARGA BEDA AGAMA DI KECAMATAN KOTA RAJA, KOTA KUPANG - Hendrik A.E Lao; Ezra Tari; Merensiana Hale (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
This paper focuses on interpersonal communication in interfaith families. Interfaith families are smallunits of society whose members are of different religions. Differences are often a source of conflict between husband and wife, including religion. In the way of life of interfaith couples, different opinions about beliefs cause problems. Differences are still unavoidable in families married to different religions. Religious differences can lead to prolonged conflicts. Although different religions, of course, the family has the right to live in peace and happiness as a family in general. However, it is undeniable that interfaith families cannot last long. Therefore, efforts are needed for families to be able to live with each other accepting differences in terms of different religions. Communication is one of the efforts to maintain family harmony. Lack of communication can cause rifts in the household. The purpose of the study was to describe the effectiveness of interpersonal communication for families of different religions. The research method used is a descriptive qualitative approach. This approach seeks to find problems and solutions in the field. Research results in interpersonal communication are communication between individuals or between groups. Interpersonal communication will be more effective if the atmosphere is equal. That is, there must be a tacit acknowledgement that both parties are equally valuable and valuable. Husbands and wives have something important to contribute. In an interpersonal relationship characterized by equality, disagreement and conflict are seen as an attempt to understand differences. This communication helps in avoiding and reducing various problems and can share knowledge and experiences with family members. There are five general qualities of interpersonal communication effectiveness for interfaith families: 1) Openness, 2) Empathy, 3) Supportive Attitude, 4) Positive Attitude, 5) Equality.